Vulnerabilidades no contexto das famílias de crianças com deficiência - Bezerra, Ana Caroline Lira (2022)
Several elements of susceptibility and vulnerability are present in the context of families of children with disabilities, such as health problems, prejudice, social inequalities, among others. Health care in view of the vulnerabilities of families is essential for a better development of children and this care needs to be worked on in the context and reality in which families live. Therefore, the concern of this research was the following: What are the vulnerabilities present in the daily lives of families of children with disabilities? The objective was to analyze vulnerabilities in the context of families of children with disabilities based on studies by Florêncio and Moreira (2021) on clarifying the concept of vulnerability. This is a descriptive study, with a qualitative approach, to be carried out in the city of Sobral/CE. This study is part of a larger research entitled: Experiences of families constituted with Children with Disabilities: Organization, Practices and Needs, approved by the Research Ethics Committee (CEP) of the Universidade Estadual Vale do Acaraú – UVA, under protocol number 2,806,799. The participants consisted of family members of children with disabilities assisted in the following services: Rehabilitation Center of the local health system; Psychosocial Care Center (CAPS); Association of Parents and Friends of the Disabled (APAE); and the House of the Autistic. Data collection took place through semi-structured interviews. 65 family members of children with disabilities participated in the research. For the analysis of the semi-structured interviews, the Content Analysis Technique - categorical analysis - proposed by Bardin (2016) was used. As this is a study involving human beings, it was guided by Resolution No. 466, of December 12, 2012, of the National Health Council. Families who agreed to participate in the study signed a Free and Informed Consent Form. In the results, Vulnerability situations wereorganized into two thematic axes and into four final categories. The first category portrays the challenges of daily life for families of children with disabilities since the discovery of the diagnosis, such as the overload of care and tasks, social and family prejudice, deprivation of leisure, economic difficulties. The second deals with the satisfaction of families with regard to children's access to the fundamental rights guaranteed to them. In the third, we have the representativeness of the diagnosis for the family, involving a whole process of acceptance, coping, and learning. And in the last category: the search for informational support as a way of conducting care. It was evident that situations of vulnerability are expressed by the need for information about the diagnosis on the part of the parents; the overload of the care process; for the difficulties faced in the routine and in the access to the rights to health and education; social inclusion and important changes in family relationships. However, managing/coping with these situations allows families to be more empowered in the face of vulnerabilities, in order to support a better quality of life for the child and his family.